Exploration of Local Wisdom-Based Physics Learning Resources in the COKSACAR Case Study - Ulfi Meiyana; Rizki Ardiawan; Fiqoh Khoeriyah; Ahmad Khoiri; Sri Jumini; Firdaus Firdaus (Variabel, 2021)
Research objectives were to (1) Know the exploration of learning resources based on local wisdom; (2) To find out that local wisdom can be used as a learning resource in Viscosity material; (3) How to grow the entrepreneurial spirit with learning resources based on local wisdom. Qualitative descriptive research method with inductive and deductive analysis techniques. Data collection methods used documentation and participatory observation. The results showed that: (1) The form of exploration of learning resources based on local wisdom in the Wonosobo area was carried out with processed food products, namely COKSACAR. COKSACAR is a processed product of Carica fruit combined with chocolate. (2) The process of making COKSACAR as a learning resource for viscosity, namely the basic concepts and factors that affect viscosity in the form of the chocolate dough viscosity, fluid substances, the temperature in chocolate processing, and additives in the chocolate dough. (3) Learning resources based on local wisdom using COKSACAR can grow the entrepreneurial spirit, including (a) Motivation through the promotion of COKSACAR products. (b) Able to cultivate self-confidence, result-oriented, risk-taking, leadership, future-oriented, and able to find original and creative and innovative ideas. Learning resources that utilize the local potential of COKSACAR can foster a spirit of learning and train students' entrepreneurial spirit